Mental Health Care Utilization and Psychiatric Diagnoses in a Sample of Military Suicide Decedents and Living Matched Controls. Issue 9 (September 2020) - Ryan, Arthur T.; Ghahramanlou-Holloway, Marjan; Wilcox, Holly C.; Umhau, John C.; Deuster, Patricia A.
Abstract : Abstract: This article examines mental health care utilization and psychiatric diagnoses among US military personnel who died by suicide. We employed an existing electronic health record dataset including 800 US military suicide decedents and 800 matched controls. Suicide decedents were more likely to have received outpatient and inpatient mental health care and to have been diagnosed with depression, bipolar, and nonaffective psychotic disorders. Younger decedents and those in the US Marine Corps were less likely to receive MH care before suicide. Given that approximately half of the suicide decedents in our sample had no mental health care visits before their death, our study suggests the need for programs to increase treatment engagement by at-risk individuals. Such programs could address barriers to care such as stigma regarding mental illness and concerns that seeking mental health care would damage a service member's career. Abstract : Supplemental digital content is available in the text.